Iron status and homeostasis across 2 competitive seasons in NCAA division I collegiate cross-country runners residing at low altitude - Goodrich, J. A.; Frisco, D. J.; Kim, S.; VanBaak, K.; Holliday, M.; Rueda, M.; Poddar, S.; Byrnes, W. C. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Inflammatory cytokines including interleukin-6 can upregulate hepcidin and decrease iron absorption. Endurance exercise is associated with transient increases in cytokines, which may alter the risk of iron deficiency (ID). This study examined whether chronic elevations in basal levels of cytokines and hepcidin were associated with ID in highly trained runners.